Changes in wheat and potato starches induced by gamma irradiation: A comparative macro and microscopic study. Issue 7 (3rd July 2017) - Atrous, Hager; Benbettaieb, Nasreddine; Chouaibi, Moncef; Attia, Hamadi; Ghorbel, Dorra
ABSTRACT: Wheat and potato starches were treated by gamma irradiation (0, 3, 5, 10, 20, 35, and 50 kGy). Apparent amylose content, gelatinization maximum consistency, swelling power, viscosity, and textural parameters decreased in potato and wheat starch pastes as irradiation dose increased. Nevertheless, the decrease of apparent amylose content and swelling power was greater in potato starch than in wheat one. High gamma irradiation doses made potato starch granules more sensitive to shear. On the other hand, no modification in the granule shape was observed by scanning electron microscopy. However, through heat-treatment, starch granules destroyed as irradiation dose increased. Consequently, the effect of irradiation on granular structure appeared to be greater in potato starch than in wheat starch.